A consistent 100-seed weight QTL with pleiotropy for seed number/plant in soybean (Glycine max L.): A consistent 100-seed weight QTL with pleiotropy for seed number/plant in soybean (Glycine max L.) - GIRIRAJ KUMAWAT; SHIVAKUMAR MARANNA; HARSHA SHRIVASTAVA; ARTI YADAV; NATARAJ VENNAMPALLY; SUBHASH CHANDRA; VANGALA RAJESH; GYANESH KUMAR SATPUTE; MILIND RATNAPARKHE; SANJAY GUPTA (Journal of Oilseeds Research, 2023)
Seed weight and seed number/plant are important determinants of seed yield in soybean (Glycine max L.). A recombinant inbred line (RIL) population of cross EC538828 x JS97-52 was phenotyped for 100-seed weight (100-SW), seed number/plant (SNPP) and seed yield/plant (SYPP) for identifying quantitative trait loci (QTL) governing these traits. Linkage analysis using SSRs from reported QTL hotspots for 100-SW identified a consistent but pleiotropic QTL on chromosome 10. The QTL showed pleiotropy for SNPP with opposite phenotypic effect, while the pleotropic QTL doesn’t affect seed yield in consistent manner.